Oral Agreements in the Agricultural Profit-Sharing System in East Kolaka, Indonesia - Andi Rizal Kadir; Sukring Sukring; Idaman idaman (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: The profit-sharing agreements that occur in Atolanu Village, East Kolaka are generally made verbally among community members. The profit-sharing system practiced by the people of Atolanu village is fundamentally based on mutual agreement according to local customs. In making profit-sharing agreements, the people of Atolanu village always do so verbally, which has the potential to cause injustice and legal uncertainty in the agreements. Objective: First, to analyse the profit-sharing concept based on mudharabah in Islamic economic law. Second, analyse the legal consequences of agreements without using the mudharabah system in Atolanu Village, Lambandia District, East Kolaka Regency. Method: the method used in this research is empirical research. A method that seeks to observe the law in its real sense or can be said to observe, examine how the law works in society, which is then approached with a qualitative research method. the approach used in this research is the statute approach, the conceptual approach. Results: the profit-sharing system in agriculture practiced The community of Atolanu village, Lambandia District, East Kolaka, still follows the old tradition-based regulations, known as 'teseng'. This oral agreement is based on the trust of both parties. Conclusion: The legal consequences of agreements made verbally or not written in the form of letters or deeds in Atolanu Village, Lambandia District, East Kolaka Regency, can pose significant legal risks, including weak evidence and proof, as well as unclear terms regarding deadlines and agreed percentages. This can result in difficulties in enforcing the rights and obligations of the parties involved in the agreement. Keywords: Teseng, Mudharabah, Oral Agreement, Legal Consequences, Sharia Economic Law